PESANTREN DAN KEMANDIRIAN EKONOMI KAUM SANTRI (Kasus Pondok Pesantren Fathiyyah Al-Idrisiyyah Tasikmalaya) - Ujang Suyatman (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2017)
Pesantren (Islamic boarding school) Al-Fathiyyah Idrisiyyah in Tasikmalaya, in addition that it is the known for its well-developed sufism teachings, the school is economically independent as it runs its own businesses. The study is focused on its paradox: how this school relate and internalize sufism teachings and enterpreneurship, educational paradigm and its economic contribution to the society. Using qualitative-descriptive, the data are collected in the multi-method technique. The reseacrh findings depict how sufism teaching principles are made as the foundation of the enterpreneurship spirit of the pupils. Through the paradigm of mechanism and organism, the education model at the pesantren consists of theoretical teachings and direct engagement to the community through its businesses that are aimed to develop economic independence.